2018
DOI: 10.1111/padm.12390
|View full text |Cite
|
Sign up to set email alerts
|

Institutional isomorphism, negativity bias and performance information use by politicians: A survey experiment

Abstract: New Public Management popularized performance measurement in public organizations. Underlying performance measurement's popularity is the assumption that it injects performance information (PI) into decision-making, thus rationalizing the ensuing decisions. Despite its popularity, performance measurement is criticized. In part, this criticism results from the limited knowledge of the conditions under which PI is purposefully used by politicians. We conducted a survey experiment based on real PI with 1,240 poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 54 publications
6
66
1
11
Order By: Relevance
“…Along these lines, both George et al () and Micheli and Pavlov () explore and identify the possible drivers of performance information use(s), with the former mainly focusing on how institutional forces influence politicians’ behaviours, and the latter exploring internal organizational dynamics, and, importantly, how and why different actors will favour different uses.…”
Section: The Articles In the Symposiummentioning
confidence: 99%
See 2 more Smart Citations
“…Along these lines, both George et al () and Micheli and Pavlov () explore and identify the possible drivers of performance information use(s), with the former mainly focusing on how institutional forces influence politicians’ behaviours, and the latter exploring internal organizational dynamics, and, importantly, how and why different actors will favour different uses.…”
Section: The Articles In the Symposiummentioning
confidence: 99%
“…Along these lines, both George et al (2019) and Micheli and Pavlov (2019) explore and identify the possible drivers of performance information use(s), with the former mainly focusing on how institutional forces influence politicians' behaviours, and the latter exploring internal organizational dynamics, and, importantly, how and why different actors will favour different uses. appear to lead to a higher intended performance information use, normative pressures (comparisons with performance standards recommended by a professional organization) encourage respondents to share contact details in order to learn more about the performance indicator.…”
Section: The Articles In the Symposiummentioning
confidence: 99%
See 1 more Smart Citation
“…According to prospect theory, people who are usually risk‐averse develop different attitudes and engage in different behaviours when they face a loss as opposed to a gain (James ; Kahneman ; Van Ryzin ). The psychological literature and political and public administration research have all indicated that people attribute more importance to, and experience stronger emotions about, negative trends or results than positive results (Rozin and Royzman ; Schwartz ; George et al ). Various studies also emphasize the negativity bias related to citizens' interpretations of performance information (James ; James and Moseley ; Olsen ).…”
Section: Citizens' Interpretations Of Performance Information: Impactmentioning
confidence: 99%
“…Here again, we cannot draw a clear-cut conclusion as to whether either the improvement or the worsening of performance influences citizens' interpretations more than the other. The marginal impact of the trend of the indicators on citizens' interpretations contradicts a large volume of work indicating that people attribute more importance to and are more passionate about negative trends or results than positive outcomes(Rozin and Royzman 2001;James 2011;Kahneman 2011;Van Ryzin 2013;Schwartz 2014;George et al 2018). Our analysis not only does not support this idea of a negativity bias but also indicates that the trends the indicators show play a marginal role in the public's interpretation of performance information.…”
mentioning
confidence: 96%